Efektivitas E-Service Quality dan Customer Feedback terhadap Keputusan Menggunakan Aplikasi Reddoorz - Afifah, Fitriani; Komariah, Kokom; Norisanti, Nor (Jurnal Ilmu Manajemen, 2020)
The purpose of this study was to determine how consumers’ decisions in using the RedDoorz application, and to find out how the effectiveness of e-service quality in the RedDoorz application as well as customer feedback on the RedDoorz application. This research uses descriptive and associative methods and uses a nonprobability sampling technique that's is purposive sampling. By distributing questionnaires to 130 respondents with a survey on the city of Sukabumi, data collection was done by collecting primary and secondary data, researchers conducted questionnaires testing using validity and reliability tests, also using the classic assumption test that is the Kolmogorov Smirnov normality test to determine residual values normal or reverse regression. The data analysis technique used is a simple correlation coefficient, multiple correlation coefficient, simple linear regression, multiple linear regression, and hypothesis testing using a partial test ( T-test) and simultaneous test ( F test). From the results of the questionnaire, analysis can be declared valid and reliable, as well as the results in testing the normality test of the total population expressed normal distribution. The results of the analysis conducted by researchers are the influence of e-service quality on decision using the RedDoorz application, also the influence of customer feedback on decision using the RedDoorz application, decision using the application can be explained by e-service quality can also be explained by customer feedback, including in the simultaneous test of e-service quality and customer feedback both influence the decision to use the RedDoorz application.